Carbon and nitrogen isotope composition of natural pastures in the dry Puna of Argentina: a baseline for the study of prehistoric herd management strategies - Samec, Celeste Tamara (2015)
This study represents an isotopic survey of modern plants developed to establish baseline isotopic values in order to explore prehistoric herd management strategies employed by the South American camelid herders that occupied the southern Andean highlands during the past 3000 years. We present carbon (δ13C) and nitrogen (δ15N) isotopic compositions of natural pastures collected from different plant communities along an altitudinal gradient in the dry Puna of Argentina. Our results show that C3 plants are the most abundant along the whole altitudinal gradient and that C3 and C4 plants exhibit a differential distribution, the latter being less abundant in those sites located above 3900 meters above sea level (masl). At the same time, plants growing at low-altitude sites with low water availability exhibit higher δ15N values than plants growing at high-altitude sites with higher water availability. These results explain the negative correlation found between altitude and South American camelid bone collagen δ13C and δ15N values published in previous studies. This work represents a fundamental step towards the building of an isotopic ecology for the dry Puna area with the ultimate goal to explore herd management strategies employed by human groups in the past. In this sense, modern plant and South American camelid tissue isotopic compositions would provide a frame of reference to interpret isotopic compositions measured on archaeofaunal remains recovered at pastoral sites, with the aim to explore mobility and pastureland use by prehistoric herders.